Matisse, "The Moroccans": seeing For Yourself (Revista Apotheke, 2021)
A New York painter and freelance teaching artist describes an experience visiting Matisse’s painting “The Moroccans” at the Museum of Modern Art with a group of young people and their families. She describes her aesthetic education methods which include encouraging museum visitors to engage deeply with works of art by noticing, asking questions, and participating in group discussion. When the visitors’ conclusions about “The Moroccans” turn out to be at odds with the museum’s wall text, they question what they should believe—their own eyes or the museum’s official interpretation of this abstract work. Connecting this experience to John Dewey’s writing about the purpose of art and the power of the perceiver to activate an art object, the author reflects on the role of museums and the sometimes conflicting priorities of public engagement and scholarly authority.